Medieval Coastal Sand Inundation in Britain and Ireland. (1st January 2015) - Griffiths, David
Abstract : HISTORICAL, ARCHAEOLOGICAL AND GEOMORPHOLOGICAL data indicate that many of the coastal dune formations of Britain and Ireland underwent significant accretion in the medieval and post-medieval periods. The changes wrought by sand-blows to settlement and agriculture were far-reaching, and in some cases devastating. Contemporary attempts to stave off their effects were in many cases the prelude to settlement shift and abandonment. The desertion of sand-inundated settlements has left a rich but fragile archaeological resource concealed under coastal sand-dunes. Exposure, deflation and erosion remain serious challenges to the management and conservation of these landscapes. Archaeological methods applied in sand-dune landscapes are reviewed, with the aim of outlining the range of techniques and approaches available for research and management.